Aplicación de estrategias metodológicas para el desarrollo de destrezas con criterio de desempeño en geografía de los estudiantes de novenos años de Educación General Básica Superior de la Unidad Educativa Juan de Velasco, 2023 – 2024. - Pilco López, Mónica Fernanda (2024)
The study sought to apply methodological techniques for building skills with performance criteria during the ninth year of EGBS at "Juan de Velasco" Educational Unit, 2023-2024. According to INEVAL (2023), the EGBS students chosen to take the Social Studies evaluation scored between insufficient and elementary achievement, indicating a need for reinforcement. A descriptive, progressive, mixed-direction methodology was adopted. The current condition was assessed using research methods and instruments. Teachers report that students struggle with distraction, a lack of accountability, a lack of use of technology and geographic tools, and a poor grasp and interpretation of maps. It is pointed out that the environment is fiscal, so there is no adequate access to resources and the material is insufficient to use ICTs. The position of the speakers indicates that learning Social Studies is essential in the integral constitution of human beings, revealing that teachers do not rely on the resources of ICT in their classes. Finally, it is concluded that students require a variety of methodological strategies that allow them to consolidate the development of skills with performance criteria in Geography, through the design and application of the methodological guide consisting of methods, resources, indicators, and evaluation, to be mediated by teachers, this requirement planned by the proposal could be achieved.